Modern approaches and methods of formation and development of management personnel in a modern IT company - E. V. Yakovleva; R. G. Poldvey (Омский научный вестник: Серия "Общество. История. Современность")
The development of an organization operating in the field of high technologies must take into account modern approaches and methods for the formation and development of management personnel. This is true for both small businesses and large companies, especially those that produce complex products or operate in high-tech businesses. In such conditions, where there is high competition and strict requirements for management and organization of activities, the desire for continuous development and technological improvement is especially important. This article defines the main methods for managing the formation and development of IT management personnel in companies.